Transcriptomic analysis of hepatocellular carcinoma reveals molecular features of disease progression and tumor immune biology. Issue 1 (December 2018) - Okrah, K.; Tarighat, S.; Liu, B.; Koeppen, H.; Wagle, M.; Cheng, G.; Sun, C.; Dey, A.; Chang, M.; Sumiyoshi, T.; Mounir, Z.; Cummings, C.; et al.
Abstract Hepatocellular carcinoma (HCC) develops in the context of chronic inflammatory liver disease and has an extremely poor prognosis. An immunosuppressive tumor microenvironment may contribute to therapeutic failure in metastatic HCC. Here, we identified unique molecular signatures pertaining to HCC disease progression and tumor immunity by analyzing genome-wide RNA-Seq data derived from HCC patient tumors and non-tumor cirrhotic tissues. Unsupervised clustering of gene expression data revealed a gradual suppression of local tumor immunity that coincided with disease progression, indicating an increasingly immunosuppressive tumor environment during HCC disease advancement. IHC examination of the spatial distribution of CD8+ T cells in tumors revealed distinct intra- and peri-tumoral subsets. Differential gene expression analysis revealed an 85-gene signature that was significantly upregulated in the peri-tumoral CD8+ T cell-excluded tumors. Notably, this signature was highly enriched with components of underlying extracellular matrix, fibrosis, and epithelial–mesenchymal transition (EMT). Further analysis condensed this signature to a core set of 23 genes that are associated with CD8+ T cell localization, and were prospectively validated in an independent cohort of HCC specimens. These findings suggest a potential association between elevated fibrosis, possibly modulated by TGF-β, PDGFR, SHH or Notch pathway, and the T cell-excluded immune phenotype. Indeed, targeting fibrosis using a TGF-β neutralizing antibody in the STAM™ model of murine HCC, we found that ameliorating the fibrotic environment could facilitate redistribution of CD8+ lymphocytes into tumors. Our results provide a strong rationale for utilizing immunotherapies in HCC earlier during treatment, potentially in combination with anti-fibrotic therapies. Liver cancer: Poor tumor immunity linked to fibrosis Anti-fibrotic drugs could help make patients with liver cancer more responsive to immune-targeted therapies. A team led by Shih-Min Huang and Mark Lackner from Genentech in South San Francisco, CA, USA, analyzed gene expression profiles in tumor samples taken from 98 people with hepatocellular carcinoma, the most common form of liver cancer. The expression analysis revealed a persistently down-modulated immune microenvironment—and the more advanced the disease, the stronger the immune suppression. The researchers also saw an association between increased expression of genes involved in fibrotic tissue scarring and diminished immune function. They therefore administered an antibody drug that blocks a key growth factor implicated in fibrosis to a mouse model of the disease. These animals showed enhanced immune function, raising the possibility of using a similar strategy in patients undergoing immunotherapy for liver cancer.